The Mechanism, Clinical Efficacy, Safety, and Dosage Regimen of Atomoxetine for ADHD Therapy in Children: A Narrative Review - Fu, Di; Wu, Dan-Dan; Guo, Hong-Li; Hu, Ya-Hui; Xia, Ying; Ji, Xing; Fang, Wei-Rong; Li, Yun-Man; Xu, Jing; Chen, Feng; Liu, Qian-Qi (Frontiers in Psychiatry, 2022)
Atomoxetine, a selective norepinephrine (NE) reuptake inhibitor, was approved for attention deficit/hyperactivity disorder (ADHD) treatment in children, adolescents and adults. We searched the database PubMed/MEDLINE (2000 to October 1, 2021). Only publications in English were considered. Atomoxetine inhibits the presynaptic norepinephrine transporter (NET), preventing the reuptake of NE throughout the brain along with inhibiting the reuptake of dopamine in specific brain regions such as the prefrontal cortex (PFC). The mechanism of action of atomoxetine also includes several new brain imaging studies and animal model studies. It is mainly metabolized by the highly polymorphic drug metabolizing enzyme cytochrome P450 2D6 (CYP2D6). Atomoxetine is effective and generally well tolerated. ADHD is often accompanied by multiple comorbidities. A series of studies have been published suggesting that atomoxetine is effective in the treatment of ADHD symptoms for children with various types of co-morbidity. In some cases, it is possible that atomoxetine may have a positive influence on the symptoms of comorbidities. Atomoxetine can be administered either as a single daily dose or split into two evenly divided doses, has a negligible risk of abuse or misuse. The latest guideline updated that clinical dose selection of atomoxetine was recommended based on both CYP2D6 genotype and the peak concentration of atomoxetine. To have a more comprehensive understanding of atomoxetine, this review sets the focus on the mechanism of action, clinical efficacy and dosage in detail, and also touches on those studies regarding adverse reactions of atomoxetine.